A 211-year River Reconstruction of the Chic-Choc and McGerrigle Mountains of the Gaspésie from Tree-rings - Pace, Alexandre (2020)
Long instrumental records are needed to serve as baselines in order to fully understand naturally occurring streamflow and climate variability, especially in this era of rapid anthropogenic climate change. In most remote parts of Canada, both instrumental streamflow and climate data are of relatively short duration, spanning approximately 50 years in duration. Barring annually laminated varved sediments, tree-ring reconstructions with their absolute dates are the only feasible way to infer streamflow and climate data of the past at an annual or sub-annual resolution in such places. Such inferred paleo-hydrological and paleo-climate data has proved useful for better natural resource management, providing a much-needed long-term context. Here we present a 211-year high-frequency tree-ring-based reconstruction of the Sainte-Anne River, Gaspésie, Québec. This reconstruction shows that the short 49-year instrumental record does not capture the full range of the natural variability of the river, especially that of the periods of sustained low flows. This river arises in the interior of the Gaspé Peninsula, a region that contains some of the highest mountains in Québec. The instrumental streamflow and climate records are particularly short in this alpine region, which is the location of the Parc national de la Gaspésie. This alpine region is the home of the critically endangered southernmost herd of caribou in Canada and many rare, endemic plants. The Sainte-Anne River is also the site of an important Atlantic salmon fishery. Hence, a longer-term moisture record can serve as a useful tool for management of these threatened fauna, flora and ecosystems.